2023
DOI: 10.1108/ijchm-06-2022-0716
|View full text |Cite
|
Sign up to set email alerts
|

What happens to abusive actors? A study of managers’ emotional responses and impression management tactics subsequent to enacted abusive supervision

Abstract: Purpose The purpose of this paper was to investigate how managers react to their own abusive supervision. Accordingly, this research identified a mechanism that managers may use to make amends for their abusive supervisory behaviors. Design/methodology/approach Two studies were designed. Study 1 was an online experimental study involving 99 full-time managers in the hotel industry that examined how managers’ internal factors moderated the relationship between enacted abusive supervision and embarrassment. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Although the motives of managerial abuse can be performance promotion (Liu et al , 2012), it causes backlash to the supervisor by increasing insubordination. Thus, organizational efforts to identify abusive leaders and provide them with leadership (Yu et al , 2020) and create positive organizational culture (Shi et al , 2023). It can prevent abusive supervision and costly employee insubordination.…”
Section: Discussionmentioning
confidence: 99%
“…Although the motives of managerial abuse can be performance promotion (Liu et al , 2012), it causes backlash to the supervisor by increasing insubordination. Thus, organizational efforts to identify abusive leaders and provide them with leadership (Yu et al , 2020) and create positive organizational culture (Shi et al , 2023). It can prevent abusive supervision and costly employee insubordination.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals are concerned about their rating in their organizations; similarly, they create general views concerning whether supervisors pay attention to their contributions and will take care of their well-being (Wang et al, 2014). Furthermore, individuals' perception of the degree accorded by their supervisor plays a major role in forging independent attachments to organizations and assists individuals to ease job stress, resolve disagreement at work and even reduce their turnover decisions (Shi et al, 2023). As a consequence, supervisor support can be regarded as a type of social-based identity that creates a feeling of responsibility to assist supervisors in reaching the set targets, including raising the standard of job activities or going beyond assigned obligations (Shanock and Eisenberger, 2006;Hwang et al, 2022).…”
Section: Theoretical Overview and Hypothesesmentioning
confidence: 99%
“…The extant hospitality management research has identified supportive supervision (e.g., Gordon et al, 2019;Quratulain & Al-Hawari, 2021) and abusive supervision (e.g., J. Park & Kim, 2019;Shi et al, 2023;Tews & Stafford, 2020;Xu et al, 2018;Yu et al, 2020) as critical management styles with contrary consequences. By focusing on supportive and abusive supervision, past research seems to be implying that supervisor behaviors are either constructive or destructive.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al, 2016), and customer orientation (see Yu et al, 2020) may alleviate the negative effects of abusive supervision on subordinates. Moreover, one study examined the influences of abusive supervision on the abuser (i.e., supervisor) and found it led to embarrassment and compensatory behaviors including apology and exemplification (Shi et al, 2023). Nevertheless, existing studies have yet examined the influences on the subordinate when supervisors compensate their abusive supervising behaviors by also being supportive.…”
Section: Introductionmentioning
confidence: 99%